Degradation kinetics of functional components of honeysuckle flowers during controlled-atmosphere heat pump drying - Lei, Luo; Bin, Yang; Wenxue, Zhu; Guangyue, Ren; Xu, Duan; Xinyan, Kang (International Journal of Agricultural and Biological Engineering, 2016)
To investigate the change law of functional components and exterior color of honeysuckle flowers (HF) during controlled-atmosphere heat pump drying, nitrogen was used as drying medium in this study to reduce the oxygen concentration. The influences of drying temperature, HF’s loading amount and oxygen concentration on chlorogenic acid content, cynaroside content and L value (on behalf of browning degree) were explored, and the degradation kinetics models of chlorogenic acid and cynaroside were constructed. The results showed that chlorogenic acid content, cynaroside content and L value decreased with the rise of temperature, HF’s loading amount and oxygen concentration. The degradation kinetics models of chlorogenic acid and cynaroside during the drying process were established through introducing an exponent r related to time t in the first order reaction kinetics equation. The models had good fitting precision and can be used to predict the degradation law of chlorogenic acid and cynaroside.Keywords: honeysuckle flowers, controlled-atmosphere heat pump drying, chlorogenic acid, cynaroside, degradation kineticsDOI: 10.3965/j.ijabe.20160904.1940Citation: Luo L, Yang B, Zhu W X, Ren G Y, Duan X, Kang X Y. Degradation kinetics of functional components of honeysuckle flowers during controlled-atmosphere heat pump drying. Int J Agric & Biol Eng, 2016; 9(4): 159－168.